COUNSELLING TEACHERS' EFFORTS IN REDUCING STUDENTS' ANXIETY LEVELS THROUGH INDIVIDUAL COUNSELING AT MAN 1 DELI SERDANG - Indriani, Ananda (BRIGHT VISION Journal of Language and Education, 2023)
This research aims to determine the efforts of guidance and counselling teachers in reducing students' anxiety level through individual counselling at MAN 1 Deli Serdang. This type of research is a descriptive qualitative research. The subjects of this research were guidance and counselling teachers, mathematics teachers and students who received individual counselling on learning anxiety. The data collection techniques include observation, interviews and documentation techniques. The data analysis carried out is data reduction, data presentation and data verification or conclusions.The results of the research showed that students in class XI MIPA-1 MAN 1 Deli Serdang experienced both internal and external learning anxiety. In general, the anxiety experienced by students is not understanding the lesson well, high curriculum objectives, subject teacher explanations that use the lecture method, causing students to feel sleepy in class, and uncomfortable classes so that students find it difficult to concentrate while learning. Taking place.Therefore, the efforts of guidance and counselling teachers are to carry out individual counselling as the main service in implementing the function of solving students' problems by optimising guidance and counselling services as the core strength in schools in order to reduce students' anxiety. Counselling guidance teachers provide individual counselling to students who experience anxiety by giving advice, suggestions and new insights, so that students can think about the good and bad effects of this anxiety, and students become more independent individuals to reduce their anxiety.